Targeting the unfolded protein response for disease intervention. (September 2015) - Rivas, Alexis; Vidal, René Luis; Hetz, Claudio
<x xml:space="preserve">Abstract</x> Introduction: The accumulation of misfolded proteins in the endoplasmic reticulum (ER) generates a stress condition that engages the unfolded protein response (UPR). The UPR is an adaptive reaction that aims to reestablish ER proteostasis by recovering the folding capacity of the cell. However, chronic ER stress results in apoptosis. Areas covered: This review focuses on discussing the emerging role of the UPR as a driver of several human pathologies including diabetes, neurodegenerative diseases and cancer. The involvement of specific UPR signaling components on different diseases is highlighted based on preclinical models and pharmacological and genetic manipulation of the pathway. Expert opinion: Therapeutic strategies directed to regulate the activity of different UPR signaling arms may reduce stress levels with a therapeutic gain. Recent drug discovery efforts have identified small molecules that target specific UPR components, providing protection on various disease models. However, important side effects are predicted in the chronic administration due to the fundamental role of the UPR in highly secretory organs such as liver and pancreas. To overcome these problems, we propose the use of combinatorial treatments of selected drugs with natural compounds that are known to modulate the ER proteostasis network.